The influence of subclonal resistance mutations on targeted cancer therapy - Schmitt, Michael W.; Loeb, Lawrence A.; Salk, Jesse J. (Nature reviews. Clinical oncology, 2016)
Key Points All cancers probably contain an enormous number of coexisting subclonal mutations; in some cases, every possible mutation could exist in at least one cell in the tumour Resistance to molecularly targeted therapies can arise from selective growth of pre-existing subclones within the bulk of the tumour that carry drug-resistance mutations and thus have a survival advantage Drug-resistance mutations can be found in variable proportions of tumour cells before therapy; their early detection enables stratification of patients to more-effective treatments and avoidance of treatments that are destined to fail Accurate identification of resistance mutations requires highly sensitive detection techniques and representative tumour sampling Routine interrogation of the subclonal genetic structure of tumours will be critical to the success of personalized cancer medicine The molecularly targeted therapy paradigm has led to improvements in the management of patients with cancer. Responses to targeted therapies are, however, mostly short-lived, owing to inherent or acquired resistance, which in most cases relates to the outgrowth of pre-existent rare subclones harbouring resistance mutations. Our current understanding of this concept is reviewed herein; how knowledge of pre-existing resistance mechanism obtained through the use of ultra-sensitive sensitive DNA-sequencing assays might be best exploited to improve personalized medicine is discussed. Clinical oncology is being revolutionized by the increasing use of molecularly targeted therapies. This paradigm holds great promise for improving cancer treatment; however, allocating specific therapies to the patients who are most likely to derive a durable benefit continues to represent a considerable challenge. Evidence continues to emerge that cancers are characterized by extensive intratumour genetic heterogeneity, and that patients being considered for treatment with a targeted agent might, therefore, already possess resistance to the drug in a minority of cells. Indeed, multiple examples of pre-existing subclonal resistance mutations to various molecularly targeted agents have been described, which we review herein. Early detection of pre-existing or emerging drug resistance could enable more personalized use of targeted cancer therapy, as patients could be stratified to receive the therapies that are most likely to be effective. We consider how monitoring of drug resistance could be incorporated into clinical practice to optimize the use of targeted therapies in individual patients.